(3GdebGHdI GdUMajI (B...(3af (B:s (3Odjd Yedj ddUMaj (B/s - (3HjGLj,TjQdj s; (3YHO GdQDa(B,(3ceGd s ((3GdbGgQI (B:s (3GdLeYjI GdeUQjI dfTQGdeYQaI h GdKbGaI GdYGdejI ,s, 1986)
(3gPG GdcJGH jbOe NdGUI JLGQH GdYOjO ef cHGQ GdUMajjf aj GdEPGYI h GdJdaRjIf h aj GdUMGaI Yf af GdebGHdI GdUMajI (B,(3Efge jYdehfc aj gPG GdcJGH cja JSLd GdedGMXGJ CKfGA GdebGHdI hcja JMUd Ydi ELGHGJ Yf CSFdJc GdUYHI (B,(3h CNjQG cja JMQQ ehVhY GdebGHdI GdUMajI hHYO Cf JbQCgPG GdcJGH JSJWjY Cf JUHM CcKQ NHQI R egGQI aj af ELQGA GdebGHdGJ GdUMajI (B. s
Keywords: (3GdebGHdI GdUMajIs; (3Odjd s